Performance of prognostic models incorporating KRAS mutation status to predict survival after resection of colorectal liver metastases. Issue 8 (August 2022) - Wong, Geoffrey Yuet Mun; Bhimani, Nazim; Mol, Barend; Diakos, Connie; de Reuver, Philip; Molloy, Mark P.; Hugh, Thomas J.
Abstract: Background: The Genetic And Morphologic Evaluation (GAME) score and modified clinical score (m-CS) are two novel prognostic models that incorporate KRAS mutation status to predict survival after resection of colorectal liver metastases (CRLM). This retrospective cohort study evaluated the performance of these two models. Methods: A total of 103 patients who underwent resection of CRLM between 2007 and 2017 and had known KRAS mutation status were included, 39 (37.9%) of whom had KRAS mutated tumours. Complete case analysis of the patients was performed according to the Clinical Risk Score (CRS), m-CS, and GAME score. The primary outcome was overall survival stratified according to low-risk and high-risk scores. Harrell's C-index and Akaike information criterion (AIC) were used to compare the discrimination of the evaluated prognostic models. Results: The GAME score demonstrated the largest difference in overall survival for patients stratified according to low-risk and high-risk groups. Harrell's C-index values for the CRS, m-CS, and GAME models were 0.583, 0.600, and 0.668, respectively. AIC values for the CRS, m-CS, and GAME models were 441, 439, and 427, respectively. Conclusion: The GAME score outperforms the CRS and m-CS in predicting overall survival after resection of CRLM in patients with known KRAS mutation status.